(untitled) (Archives of Criminology, 2023)
Resurgent populism – with crime as a core theme - is depicted as a dangerous perversion of liberal democracy. But by avoiding a definition of populism, critics tend to simply conflate populism with contemporary right-wing authoritarianism. Academic analysis, including criminological, is not free of such tendencies. After a brief consideration of criminology’s engagement with penal populism and the recent spread of a more far-reaching authoritarian political populism, the article argues for the need to more carefully conceptualise populism. Theoretical clarity is needed for assessing the character of contemporary populism; for grasping its drivers in, for example, neo-liberal globalization and what Crouch calls “post democracy”; and for discerning its possible future trajectories, progressive as well as regressive. It is also argued that simple denunciations of populism often reflect a complacent liberal mentality that contributes to political disaffection fuelling populist movements, and overlooks legitimate grievances, including the (often criminal) failings of liberal institutions. Rather than being a political aberration, populism, it is argued, should be seen as a “normal” dimension of democratic politics with implications for criminal policy (as well as politics at large).